IDENTIFIKASI PERMASALAHAN-PERMASALAHAN DALAM PEMBELAJARAN IPS - Rahmawati, B. Fitri; Zidni, Zidni (Universitas Hamzanwadi, 2019)
Social studies are one of the subjects that are taught in an integrated approach at the junior high level. This integrated learning raises its own problems in social studies learning. The purpose of this study is to identify problems in sociall studies learning. The method used is a qualitative method. the informants used were teachers and students from seven SMP/MTs. Data collection methods are interviews, observation and documentation. Data analysis uses descriptive analysis. Based on the results of the study, four problems can be identified namely students' disruptive behavior, lack of learning facilities and infrastructure, teachers lack understanding of material outside their field of learning and less varied learning methods. The disruptive behavior of students identified is wandering and playing when learning takes place, is difficult to manage, does not do the assignments, makes noise in class, does not pay attention, is sleepy, and talks. While learning facilities and infrastructure which are considered still lacking are books and learning media. The teacher also feels difficulty in understanding subject matter outside his field and the learning methods used are less varied because they use the lecture method more.